Rhinoplasty with Recycled Dorsum Preservation: Technique and Outcomes - Rodriguez, Carlos A.; Al-Sakkaf, Ali M.; Verbauvede, Mauricio (Archives of Plastic Surgery, 2022)
Rhinoplasty is one of the first surgical procedures described with evidence in the history of medicine. At first, these were performed for the reconstruction of traumatic defects caused by punishments, sequels of war, and then it had been reused after suffering from diseases such as syphilis. Many techniques have been developed from the need of aesthetics outcomes in this field.The objective of our work is to describe a modified approach of recycled dorsum preservation procedure that we have proposed as a safe and reliable technique.In this work, we have showed that this technique has a marked advantage of preserving the natural tissue with satisfactory postoperative result. We had no functional complications up to date. We recommend that every specialist in the field of rhinoplasty should be able to use it as a reproducible and feasible alternative.
Keywords: rhinoplasty; nose; hypertrophy; nasal septum